Sinonasal inverted papilloma associated with squamous cell carcinoma - But-Hadzic, Jasna (Versita, Warsaw, 2011)
BACKGROUND: The aims of the study were to review single-institution experiences with sinonasal inverted papilloma associated with squamous cell carcinoma (IP/SCC), to analyze the presence of human papillomavirus (HPV) and to evaluate the role of radiotherapy. PATIENTS AND METHODS: Five patients with IP/SCC were identified in the prospective institutional databases (1995–2005) and HPV status was determined in all five tumors. RESULTS: Four out of five patients had T3-4 tumors; no nodal involvement was seen in any of them. Four patients had curative surgery, supplemented in three of them with radiotherapy. Debulking surgery was performed in the patient with a non-resectable tumor followed by radical radiotherapy. Tumor was controlled locally in three patients at 8, 46 and 58 months post-surgery. Local failure occurred in two patients: after endoscopic resection of a T1 tumor (the recurrent tumor was successfully salvaged with additional surgery) and in a patient with an inoperable tumor. No regional or distant metastases occurred. HPV status was determined in all five tumors and three of them were found positive for HPV type 11. CONCLUSIONS: In operable sinonasal IP/SCC, upfront surgery and postoperative radiotherapy to the tumor bed with dose levels comparable to those used for invasive SCC are recommended. For non-resectable disease, radical radiotherapy to a dose of 66–70 Gy could be of benefit.